Biomimetic Dendrimer–Peptide Conjugates for Early Multi‐Target Therapy of Alzheimer's Disease by Inflammatory Microenvironment Modulation. Issue 26 (17th May 2021) - Liu, Peixin; Zhang, Tongyu; Chen, Qinjun; Li, Chao; Chu, Yongchao; Guo, Qin; Zhang, Yiwen; Zhou, Wenxi; Chen, Hongyi; Zhou, Zheng; Wang, Yu; Zhao, Zhenhao; et al.
Abstract: Current therapeutic strategies for Alzheimer's disease (AD) treatments mainly focus on β‐amyloid (Aβ) targeting. However, such therapeutic strategies have limited clinical outcomes due to the chronic and irreversible impairment of the nervous system in the late stage of AD. Recently, inflammatory responses, manifested in oxidative stress and glial cell activation, have been reported as hallmarks in the early stages of AD. Based on the crosstalk between inflammatory response and brain cells, a reactive oxygen species (ROS)‐responsive dendrimer–peptide conjugate (APBP) is devised to target the AD microenvironment and inhibit inflammatory responses at an early stage. With the modification of the targeting peptide, this nanoconjugate can efficiently deliver peptides to the infected regions and restore the antioxidant ability of neurons by activating the nuclear factor (erythroid‐derived 2)‐like 2 signaling pathway. Moreover, this multi‐target strategy exhibits a synergistic function of ROS scavenging, promoting Aβ phagocytosis, and normalizing the glial cell phenotype. As a result, the nanoconjugate can reduce ROS level, decrease Aβ burden, alleviate glial cell activation, and eventually enhance cognitive functions in APPswe/PSEN1dE9 model mice. These results indicate that APBP can be a promising candidate for the multi‐target treatment of AD. Abstract : A multi‐target nanoconjugate is developed to target the Alzheimer's disease microenvironment in the early stage. Synergistic therapeutic effects are achieved by scavenging reactive oxygen species, restoring cellular antioxidant capacity, polarizing microglia phenotype, inhibiting formation of β‐amyloid plaques, and recovering immunologic function based on the functional polymers and nuclear factor (erythroid‐derived 2)‐like 2 activating peptide. Cognitive functions are enhanced in APPswe/PSEN1dE9 model transgenic mice after treatment.